Incidence of Seropositivity for Cytomegalovirus in Skin Graft Donors at the Skin Bank of the University of the São Paulo Medical School - Junqueira, Jader Joel Machado; Eras, Aline Estefanes; Santos, Vera Aparecida dos; Polo, Eugênio Ferramundo; Herson, Marisa Roma (Brazilian Journal of Transplantation, 2007)
Introduction: Considering the likely link between the use of cytomegalovirus (CMV) infected skin grafts and the development of severe disease in immunocompromised recipients, we analysed the incidence of IgM and IgG anti-CMV antibodies of skin graft donors of University of São Paulo Medical School Skin Bank. Purpose: To analyze the incidence of soropositive skin graft donors for IgM and IgG anti-CMV antibodies at the University of São Paulo Medical School Skin Bank. Method: We performed a retrospective study in 112 screening results from skin graft donors at the Skin Bank of the University of São Paulo Medical School from 2001 to 2006. Results: None of the serum samples presented IgM anti-CMV, while IgG anti-CMV was found in 91.07% in this screening. 102 positive donors for IgG anti-CMV, IgM anti-CMV were negative in 59 cases (58%); in 43 cases (42%) the IgG screening was not performed. 10 negative donors for IgG anti-CMV, IgM anti-CMV were negative in 5 cases (50%), and in 5 (50%) cases, the IgG screening was not performed as well. Conclusion: Considering the high IgG anti-CMV antibody rates in skin graft donors and the morbidity as acute disease in immunocompromised hosts, this study outlines the importance of a careful screening including CMV screening in donors as routine in tissue and especially in skin banks.